Family institution and change of reproductive behaviour patterns of Russians in the formation of a new socio-gender order and country demographic environment - G. G. Sillaste (Цифровая социология)
The article is devoted to the study of the family institute and models of reproductive behaviour of the Russian population in the formation of a new sociо-gender order and demographic environment. The article considers the demographic situation in Russia, analyses the peculiarities of birth rate and the problem of interethnic marriages. The dependence and interrelation between changes in society and the socio-gender order as its constituent are also investigated. Special attention is paid to the anti-family policy of the West being an instrument of the socio-gender strategy. The article presents the research results and statistical data that allow us to draw conclusions about the impact of socio-gender changes on the family institution and reproductive behaviour of Russians. Finally, with the help of the analysis, we comprehend that in the formation of the new socio-gender order and demographic environment of the country, the institution and reproductive behaviour patterns of the citizens are undergoing significant transformations. These changes require an in-depth study and understanding in order to develop effective measures to support the family institution and increase the birth rate in Russia. The paper examines in detail the peculiarities of the Russian demographic situation, including analysis of the birth rate and problems of interethnic marriages. The author reveals the dependence and interrelation between the socio-gender changes and reproductive behaviour of the Russians. The study is valuable to understand current structural and value-based changes of the family as a social institute, its subjectivity and to develop support measures for families and to increase the birth rate. The article may be useful for specialists in demography, sociology, psychology, and other related sciences.